A Study On The Effect Of Extreme Rainfall Intensity On Slope Stabilty Using Physical Based Modelling - Zaki, Muhammad Hazwan (Universiti Sains Malaysia, 2019)
This study focused on assessing the effect of extreme rainfall intensity to slope stability using a physical based modelling. In this study, identified extreme rainfall intensity are modelled in a physical model with a measurement of Volumetric Water Content and Matric Suction within the slope. Selected extreme rainfall intensity is 60 mm/hr which the heaviest hourly rainfall intensity at Sarawak on 3rd of January, 2016 and 80 mm/hr which in Penang on 10th October, 2016. The simulation is conducted in a 4 different cases and parameter. The duration of the simulated rainfall is 6-hour. The overall trend of the matric suction measurement in each cases is increasing with a few exceptions of tensiometer that shows decreasing value. After the rain simulation stopped, the matric suction decreased rapidly and remain stagnant follow by a significant dropping significantly. For the volumetric water content, there is a similar increase in the trend during the rainfall simulation. However, there is difference in term of initial and increment of water content for different part of the slope. for the lower part of the slope, the initial water content is much higher which at 60 – 70 % with an increment of 15 – 20 % uring the rainfall simulation. While for the lower part are at 20 -25 % with a slight increment of 5-7 % during rainfall simulation. For all cases the failure had been occurred but on a different time and volume of mass wasting. It shows that the increased in slope inclination angle and rainfall intensity would affect the slope stability. Numerical analysis is done to model the cases in Geostudio software.